RECEIVING INFORMATION ON THE INSTAGRAM APPLICATION WHEN STAY AT HOME AND WORK FROM HOME - Syatantra Rahutama (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The number of active Instagram application users every day reaches more than 500 million, and Instagram application users who upload nearly 500 million more stories every day. So that the flow of information that is shared by one user to another is very large, and when the CORVID 19 outbreak hit in various countries, users are treated to realtime information on the Instagram application. So when the government implies that people are only at home, Instagram application users can still receive information. Instagram application users can access information and also get entertainment from applications above 50%, measuring the attitude of receiving information from Instagram application users on smart phones using the Technology Acceptance Model (TAM) and by using ease, usability and attitude variables. The results of the analysis of the three variables are from the ease of making posts and also uploading photos so that stories and feeds have not been felt by some users, which is indicated by a value of 0.40 on the Ease of Attitude e1 → e13, namely external factors. But overall users take advantage of receiving information through the Instagram application.